THE EFFECT OF LEVERAGE, LIQUIDITY, AND FIRM SIZE ON DIVIDEND POLICY - Angela, Maria Goretti; Daryanti, Sri (International Journal of Application on Economics and Business, 2023)
The purpose of this research is to measure the effects of leverage, liquidity, and firm size on the dividend policy of a manufacturing company listed on the Indonesian Stock Exchange (IDX) from 2018 to 2020. Purposive sampling was applied in this study to pick 43 organizations that met the sample criteria throughout a three-year period from 2018 to 2020, totaling 129 samples. The double linear regression approach with eviews software 12 was used to process the data. Research shows that independent variables leverage, liquidity, and corporate size are simultaneously affecting dependent variable of dividends policy. The result of partial research suggests that leverage with proxy DAR, liquidity with proxy CR does not affect the dividend policy with proxy DPR. Whereas the firm size with proxy SIZE affects the dividend policy.